2023
DOI: 10.1002/ejhf.2947
|View full text |Cite
|
Sign up to set email alerts
|

Global longitudinal strain predicts clinical outcomes in patients with heart failure with preserved ejection fraction

Abstract: AimsPatients with heart failure with preserved ejection fraction (HFpEF) are at high risk for hospitalization and mortality and many of these patients experience a deterioration in left ventricular ejection fraction (LVEF) over time. Global longitudinal strain (GLS) is a sensitive marker of myocardial dysfunction that could help predict risk for future events in this population. We assessed whether GLS can predict adverse clinical outcomes and future deterioration in LVEF in patients with HFpEF.Methods and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…The study inclusion criteria, and the definition of HFpEF, were similar to those used in the PARAGON-HF trial 4 and therefore it was not surprising that, as mentioned in the supplementary material, the clinical characteristics of their population were rather similar to other HFpEF trials and recent major registries in Europe and North America. 3 The results provide additional data justifying some enthusiasm in using speckle tracking echocardiography to improve the characterization of the HF population. Several previous studies have shown that GLS is really a need and an additive parameter to LVEF.…”
mentioning
confidence: 76%
See 4 more Smart Citations
“…The study inclusion criteria, and the definition of HFpEF, were similar to those used in the PARAGON-HF trial 4 and therefore it was not surprising that, as mentioned in the supplementary material, the clinical characteristics of their population were rather similar to other HFpEF trials and recent major registries in Europe and North America. 3 The results provide additional data justifying some enthusiasm in using speckle tracking echocardiography to improve the characterization of the HF population. Several previous studies have shown that GLS is really a need and an additive parameter to LVEF.…”
mentioning
confidence: 76%
“…Several previous studies have shown that GLS is really a need and an additive parameter to LVEF 5 . In Brann et al ., 3 59% of the HFpEF population had an abnormal GLS (cut‐off of 15.8%) despite a preserved ejection fraction. An important message, out of the risk of event associated with lowest value of GLS, comes from the 1.9‐fold increased risk for LVEF deterioration.…”
mentioning
confidence: 93%
See 3 more Smart Citations